1992
DOI: 10.1111/j.1532-5415.1992.tb01850.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypnotics, Sleep, and Mortality in Elderly People

Abstract: Earlier reported relationships between excess mortality and use of medication for sleep are replicated in this study. Among elderly people, however, this relationship does not derive from the pharmacological characteristics of prescription hypnotics. Rather, it appears that reported self-medication to promote sleep, using a variety of non-sedative products, provides an epidemiological "marker" for a group within which levels of morbidity and mortality are particularly high. Excess mortality associated with ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
66
4

Year Published

2000
2000
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(73 citation statements)
references
References 19 publications
3
66
4
Order By: Relevance
“…Previous studies have been inconsistent, with some studies observing significant relationships between hypnotic prescriptions and mortality [16,[20][21][22][23][24][25]37] and others not [16][17][18][19]. Our findings suggest that these differences are probably largely due to failure to take into account confounding associations, notably common affective symptoms and sleep complaints, although other factors such as study design, participant age, and class of hypnotics probably also influence study outcome.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…Previous studies have been inconsistent, with some studies observing significant relationships between hypnotic prescriptions and mortality [16,[20][21][22][23][24][25]37] and others not [16][17][18][19]. Our findings suggest that these differences are probably largely due to failure to take into account confounding associations, notably common affective symptoms and sleep complaints, although other factors such as study design, participant age, and class of hypnotics probably also influence study outcome.…”
Section: Discussioncontrasting
confidence: 48%
“…Four observational studies in young adults [16,17] and elderly people [18,19] found no significant associations between hypnotics and all-cause mortality. Other studies reported a significant association with excessive all-cause deaths in adults [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies, [1][2][3][4][5][6] though not all, [7][8][9][10] reported that both long and short sleep duration increased risk of death. However, there have been only a few studies controlling for various relevant confounding factors.…”
mentioning
confidence: 99%
“…3,5,9,19 Indeed, there is neither clear definition nor established measure of the quality of sleep, and some studies indicated that insomnia was not associated with increased mortality. 4,10,20,21 The third limitation is that background psychological factors were not considered. Sleep patterns are known to be associated with psychological factor.…”
mentioning
confidence: 99%
See 1 more Smart Citation